Implementation of Creative Problem Solving on Mathematical Creative Thinking Ability Viewed from Adversity Quotient (Jurnal Pelangi : Research of Education and Development, 2023)
The ability to think creatively in learning mathematics is an ability that stimulates students to find various solutions or ideas for solving mathematical problems. This study will examine the literature using the Systematic Literature Review regarding how to implement the Creative Problem-Solving learning model on students' mathematical creative thinking abilities when viewed from the Adversity Quotient. The literature criteria used in this study are journal articles indexed by Sinta or Google Scholar using Publish or Perish with the year of publication 2014 - 2023. The purpose of this research is to describe various kinds of literature that are relevant to the implementation of the Creative Problem-Solving learning model on thinking skills. students' mathematical creativity when viewed from the Adversity Quotient. By doing this research, it can provide information related to the implementation of the Creative Problem-Solving learning model on students' mathematical creative thinking abilities when viewed from the Adversity Quotient.